Utilization of Google Classroom-Based Learning Management System in Learning - Hamzarudin Hikmatiar; Dwi Sulisworo; Mentari Eka Wahyuni (Jurnal Pendidikan Fisika, 2020)
This study used a case study methodology to find out and collect information relating to the use of Google Classroom in learning in previous research articles. Based on the results of the information obtained are made in the form of table with the aim to determine the effectiveness of the use of Learning Management System based on Google Classroom in learning and the feasibility of Learning Management System based on Google Classroom as a learning media.Data from previous research results that have been obtained can be concluded that learning used Google Classroom is very effective,, because Google Classroom gets a lot of positive responses from students and other users. The feasibility of Google Classroom as a learning mediashows of excellent validation results, so it can be said to be feasible as a learning media.Keywords: Google Classroom, Learning Manegement System, Learning Penelitian ini menggunakan metodelogi studi kasus untuk mencari dan mengumpulkan informasi yang berkaitan dengan penggunaan Google Classroom dalam pembelajaran pada artikel penelitian sebelumnya. Berdasarkan hasil dari informasi yang diperoleh, kemudian dibuat dalam bentuk tabel dengan tujuan untukmengetahui efektifitas penggunaan Learning Management System berbasis Google Classroom dalam pembelajaran dan kelayakan Learning Management System berbasis Google Classroom sebagai media pembelajaran. Data hasil penelitian sebelumnya yang telah diperoleh dapat disimpulkan bahwa pembelajaran menggunakan Google Classroom sangat efektif, karena Google Classroom banyak mendapatkan respon positif dari siswa, mahasiswa, dan pengguna lainnya. Kelayakan Google Classroom sebagai media pembelajaran menunjukan rata-rata hasil validasi yang sangat baik, sehingga dapat dikatakan layak sebagai media pembelajaran.Kata kunci: Google Classroom, Learning Manegementsystem, Pembelajaran